2014
DOI: 10.1371/journal.pgen.1004302
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Modulates Clearance of Alpha-Synuclein Inclusions in a Yeast Model of Parkinson's Disease

Abstract: Alpha-synuclein (aSyn) is the main component of proteinaceous inclusions known as Lewy bodies (LBs), the typical pathological hallmark of Parkinson's disease (PD) and other synucleinopathies. Although aSyn is phosphorylated at low levels under physiological conditions, it is estimated that ∼90% of aSyn in LBs is phosphorylated at S129 (pS129). Nevertheless, the significance of pS129 in the biology of aSyn and in PD pathogenesis is still controversial. Here, we harnessed the power of budding yeast in order to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(137 citation statements)
references
References 95 publications
8
124
0
1
Order By: Relevance
“…This depends on α-synuclein phosphorylation (Basso et al, 2013; Tenreiro et al, 2014), and can be interrupted by genetic manipulation ( e.g ., α-synuclein-A30P) (Outeiro and Lindquist, 2003; Dixon et al, 2005; Sharma et al, 2006). Upon high expression levels α-synuclein forms cellular aggregates in a nucleation-dependent manner, which starts at the plasma membrane and eventually leads to cytoplasmic inclusions (Outeiro and Lindquist, 2003).…”
Section: Yeast Models Expressing Neurotoxic Proteinsmentioning
confidence: 99%
“…This depends on α-synuclein phosphorylation (Basso et al, 2013; Tenreiro et al, 2014), and can be interrupted by genetic manipulation ( e.g ., α-synuclein-A30P) (Outeiro and Lindquist, 2003; Dixon et al, 2005; Sharma et al, 2006). Upon high expression levels α-synuclein forms cellular aggregates in a nucleation-dependent manner, which starts at the plasma membrane and eventually leads to cytoplasmic inclusions (Outeiro and Lindquist, 2003).…”
Section: Yeast Models Expressing Neurotoxic Proteinsmentioning
confidence: 99%
“…We hypothesized that this may reflect the subpopulation of AD subjects with concomitant LB pathology, and found that the mismatch (α-syn–p-tau 181 -Mis) between these two markers both correlated with worse cognitive outcomes, and improved the association of the t-tau/Aβ 42 ratio with these measures when included in the model [17]. Importantly, most α-syn present in LBs is highly phosphorylated, especially at serine 129 (pS129) [15, 2022], which is thought to alter aggregation and toxicity of α-syn[23, 24]. Notably, the CSF pS129 was significantly higher in PD patients than in healthy controls, and correlated with PD severity[16, 25], suggesting it may serve as a marker of PD pathology independently of total α-syn, which tends to be lower in the CSF of PD patients[18, 2629].…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that pS129 reduces αSyn toxicity and promotes its macroautophagic clearance [195]. However, other studies have observed that pS129 increases the toxicity of αSyn and promotes aggregation [171,193].…”
Section: Ampk Activation As a Treatment Strategy For Pdmentioning
confidence: 99%